A95 OUTCOMES OF ERCP UNDER CONSCIOUS SEDATION COMPARED TO GENERAL ANESTHESIA: A PRE-POST RETROSPECTIVE COHORT REVIEW. (21st February 2022) - Greaves, G E; Yee, B; Harding, K G; Nguyen, V C; Parker, B; Perren, J; Richardson, W; Bak, A W; Perini, R; Jowhari, F; Tai, T
Abstract: Background: Endoscopic retrograde cholangiopancreatography (ERCP) is a diagnostic and therapeutic procedure used to address pathologies of the pancreatic and biliary systems. ERCP performed under conscious sedation (CS) is the current standard of care but is limited by patient movement and agitation, especially in the context of lengthy or technically complex cases. Recent literature suggests that general anesthesia (GA) may optimize patient comfort and safety while reducing complications such as pancreatitis, perforation, and mortality. In October 2017, Kelowna General Hospital (KGH) transitioned the standard anesthesia modality for ERCP from CS to GA. Aims: To investigate differences in complications and patient outcomes for ERCP performed under CS (n=1334) before the practice change compared to GA (n=899) after the practice change. Methods: Our study is a pre-post retrospective chart review of 2, 233 patients who underwent ERCP between 2015 and 2020 at KGH. Demographic, clinical, procedural and outcome data were extracted from patient charts, and the data in CS and GA groups were compared using univariate statistical analysis. Results: Preliminary results show rates of post-ERCP pancreatitis (6% vs. 4%; p=0.018) and rates of procedure failure (8% vs. 3%; p<0.001) were statistically significant and higher under CS before the practice change compared to under GA afterwards, respectively. The 30-day mortality rates, ICU transfer rates, return rates post-discharge, and rates of cholangitis were similar. Our study showed improvements in several patient safety outcomes, including lower procedure failure rates and lower post-ERCP pancreatitis rates with ERCP performed under GA compared to CS. Conclusions: Performing ERCP under GA rather than under CS is a valuable practice change that should be considered by ERCP-related programs across all health authorities due to its potential to optimize both patient comfort and safety significantly. The reduction in complication rates may have implications for net cost savings in the long term. Funding Agencies: Kelowna General Hospital Foundation, Interior Health